As you like it: Explaining the popularity of life‐cycle funds with multi cumulative prospect theory. Issue 2 (10th July 2019) - Graf, Stefan; Ruß, Jochen; Schelling, Stefan
Abstract: Life‐cycle (or target‐date) funds are funds, which typically decrease their risk exposure over time. They have been very successful in many countries, particularly in the segment of old age provision. However, Expected Utility Theory (EUT) cannot explain their popularity. Moreover, recent results of Graf (2016), imply that not only EUT but also its behavioral counterpart Cumulative Prospect Theory (CPT) is often not able to explain the popularity of these products, since for each life‐cycle fund a corresponding balanced fund can be constructed, which is preferable from the investor's perspective in most circumstances. In a recent paper, Ruß and Schelling (2018), have argued that potential future changes in an investment's value already impact the decision of long‐term investors at outset. Based on this, they have introduced Multi Cumulative Prospect Theory (MCPT), which is based on CPT and considers the subjective utility generated by annual value changes. This paper shows that for MCPT‐investors, life‐cycle funds are typically more attractive than their corresponding balanced funds since they reduce the potential losses toward the end of the investment horizon. Hence, our findings provide an explanation for inferior decisions in old age provision. This can serve as a basis to improve such decisions.